ANALISIS PENGETAHUAN DAN MINAT TERHADAP PENGGGUNAAN KOSMETIKA SUNSCREEN PADA REMAJA USIA 19 – 23 TAHUN - Rahmanita Wahyuni; Nieke Andina Wijaya; Oktaverina Kecvara Pritasari; Dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2024)
Teenagers are an age group that often do outdoor activities and their skin is still sensitive and susceptible to the negative effects of sun exposure. Therefore, teenagers' knowledge and interests greatly influence the use of sunscreen cosmetics. The aim of this research is to determine the knowledge and interest of teenagers in using sunscreen cosmetics in Bungurasih Village. This type of research is quantitative descriptive with questionnaire data collection techniques via Google Form with research objects totaling 45 respondents and the data analysis method uses multiple linear regression. Based on the results of data processing, the level of knowledge includes 4 elements, namely Knowledge, with the highest value of 53%, the element of understanding (Comprehention) with the highest value of 62%, the element of Analysis (Analysis) with the highest value of 60%, and the element of Evaluation (Evaluation) with the highest score of 52%. and interest factors, there are 3 factors, namely cultural factors with the highest value of 47%, personal factors with the highest value of 51%, and social factors with 54%. Meanwhile, there are 2 indicators for the use of sunscreen cosmetics, namely the intention to use sunscreen cosmetics with the highest value of 64%, and the attitude indicator for using sunscreen cosmetics with the highest value of 69%. Therefore, it is concluded that teenagers aged 19 - 23 years know enough about sunscreen cosmetics and are good at using sunscreen cosmetics. Keywords: Teenager, cosmetics, sunscreen